Effect of high temperature drying with load on reduction of residual stress and correction of warp of Japanese cedar lumber. Issue 1 (3rd January 2023) - Jiang, Zhuoting; Yamamoto, Hiroyuki; Matsuo-Ueda, Miyuki; Yoshida, Masato; Dohi, Motoo; Tanaka, Kento; Konishi, Hirokazu
Abstract: While sawing logs along the pith to produce lumber, warps would occur in lumber due to the release of residual stress. Correction sawing should be performed to correct warps, so warps decrease the yield of lumber. Therefore, it is crucial to find a way to produce straight lumber without correction sawing. The present study focused on a series of high temperature drying with load, and it was confirmed that residual stress was eliminated, and warp was corrected after a series of high temperature drying with load. Besides, the optimal schedule conditions of high temperature drying were determined. After 6 months of storage, the treated lumber remained straight and residual stress in lumber did not recover. By applying high temperature drying with load to warped lumber, it is possible to dry lumber and correct the warps at the same time.